2012
DOI: 10.1021/nn300385p
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Self-Assembly of Amphiphilic Semiconducting Polymers into Isolated, Bundled, and Branched Nanofibers

Abstract: Herein, we report a high-yield click synthesis and self-assembly of conjugated amphiphilic block copolymers of polythiophene (PHT) and polyethylene glycol (PEG) and their superstructures. A series of different length PHT(m)-b-PEG(n) with well-defined relative block lengths was synthesized by a click-coupling reaction and self-assembled into uniform and stably suspended nanofibers in selective solvents. The length of nanofibers was controllable by varying the relative block lengths while keeping other dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
177
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(190 citation statements)
references
References 58 publications
(85 reference statements)
13
177
0
Order By: Relevance
“…A variety of structurally diverse π-conjugated systems have been incorporated into RCPs including oligophenylene, 9 oligo(pvinylenephenylene), 10 oligo(p-benzamide), 11,12 polyfluorenes, 13,14 polythiophenes, 15,16 and poly(phenylquinolone). 17−19 Additionally, naturally occurring and synthetic helical macromolecules have been coupled with conventional random-coil polymers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…A variety of structurally diverse π-conjugated systems have been incorporated into RCPs including oligophenylene, 9 oligo(pvinylenephenylene), 10 oligo(p-benzamide), 11,12 polyfluorenes, 13,14 polythiophenes, 15,16 and poly(phenylquinolone). 17−19 Additionally, naturally occurring and synthetic helical macromolecules have been coupled with conventional random-coil polymers.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It was observed that the H4T1 amphiphilic diblock copolymer adopted random conformation in Figure 1a. 31 However, with increasing CH 3 OH solvent volume, the onedimensional nanofiber-like structure of H4T1 amphiphilic block copolymer with approximate 10 nm in width and length up to ∼500 nm (Figure 1b,c), and even a continuous, periodic lamellar structure ( Figure 1d) were observed. The bright and dark parts represented the P3HT-rich and P3TEGT-rich domains in the film respectively, driven by P3HT and P3TEGT crystallization for their different polarity of side chains and nanoscale phase separation.…”
Section: ■ Results and Discussionmentioning
confidence: 96%
“…Furthermore, the efficient PL quenching of H4T1 in DCB/CH 3 OH solvents was also indicative of tightly packed thiophene chains and strong interchain coupling in the polymer chains assemblies. 31 Earlier work on amphiphilic rod−rod diblock copolymers and their aggregation in mixtures of selective and nonselective solvents behavior was also processed in previous reports of Scherf. 33,34 A crucial requirement for high performance device was providing an efficient way to control the ordering of H4T1 amphiphilic block polymers with broadening optical absorbance in solid state.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…insulating blocks as for example PMMA (P3HT-b-PMMA), [224] or poly(2-vinylpyridine) (P3HT-b-P2VP, [225][226][227][228][229] or P4VP (P3HT-b-P4VP), [230][231][232] or PEO (P3HT-b-PEO), [233][234][235][236][237][238][239][240][241][242] or polylactides (P3HT-b-PLA), [243] or polyacrylic acids (P3HT-b-PAA). [244,245] Also more special block copolymer with P3HT block were reported as for example azobenzene liquid crystalline mesogen, 6-(4-((4-methoxyphenyl)diazenyl)phenoxy)hexyl methacrylate (MMAZO) incorporated into a block copolymer with P3HT.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%